Alpha-mannosidosis caused by toxic plants in ruminants of Argentina - Cholich, Luciana Andrea (2021)
It is well known that several of the swainsonine-containing plant species found widespread around the world have a negative economic impact in each country. In Argentina, most of the information on the poisonous plant species that produce α-mannosidosis is published in Spanish and thus not available to most English speaking researchers interested in toxic plants. Therefore, the aim of this review is to summarize the information about swainsonine-containing plants in Argentina, which are extensively distributed throughout different ecoregions of the country. To date, five species from three genera have been shown to induce α-mannosidosis in livestock in Argentina: Ipomoea carnea subsp. fi stulosa, Ipomoea hieronymi subsp. calchaquina (Convolvulaceae), Astragalus garbancillo, Astragalus pehuenches (Fabaceae), and Sida rodrigoi (Malvaceae). These species contain the indolizidine alkaloid swainsonine, which inhibits the lysosomal enzyme α-mannosidase and consequently affects glycoprotein metabolism, resulting in partially metabolized sugars. The prolonged consumption of these poisonous plants produces progressive weight loss and clinical signs related to a nervous disorder, characterized by tremors of head and neck, abnormalities of gait, difficulty in standing, ataxia and wide-based stance. Histological lesions are mainly characterized by vacuolation of different cells, especially neurons of the central nervous system. The main animal model used to study α-mannosidosis is the guinea pig because, when experimentally poisoned, it exhibits many of the characteristics of naturally intoxicated livestock.